2020
DOI: 10.1002/smll.202004487
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Quantum Rods, Covering Full Visible Range for Display and Lighting Application

Abstract: Recently, quantum rods (QRs) have been studied heavily for display and lighting applications. QRs offer serious advantages over the quantum dots such as higher light out‐coupling coefficient, and polarized emission. The QR enhancement films double liquid crystal display efficiency. However, it is still a challenge to synthesize good quality green (λem ≈ 520 nm) and blue (λem ≈ 465 nm) emitting QRs, due to very large bathochromic shift during the shell growth. Furthermore, until now, the presence of cadmium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…The method is based on Cd to Zn cation exchange in a one‐pot postsynthetic procedure. [ 36 ] These QRs show better thermal stability in comparison to the conventional CdSe/CdS core–shell QRs. The details can be found in ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is based on Cd to Zn cation exchange in a one‐pot postsynthetic procedure. [ 36 ] These QRs show better thermal stability in comparison to the conventional CdSe/CdS core–shell QRs. The details can be found in ref.…”
Section: Resultsmentioning
confidence: 99%
“…The details can be found in ref. [ 36 ] . The QRs for the LED application, as stated above, has three basic problems, i.e., the emission wavelength, low PLQY in solid (film) state, [ 37 ] and stability (thermal and photo).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, NRs can be assembled into highly ordered arrays, where their parallel alignment enables a high degree of emission polarization that can be applied to improve efficiency of liquid crystal displays. [ 3–6 ] One prominent example of brightly emitting semiconductor NRs are core–shell heterostructured nanoparticles termed “dot‐in‐rod,” which can be produced by seeded growth synthesis. In 2007, Carbone et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NRs can be assembled into highly ordered arrays, where their parallel alignment enables a high degree of emission polarization that can be applied to improve efficiency of liquid crystal displays. [3][4][5][6] One prominent example of brightly emitting semiconductor NRs are core-shell heterostructured nanoparticles termed "dot-in-rod," which can be produced by seeded growth synthesis. In 2007, Carbone et al and Talapin et al independently reported a type I heterostructure comprising CdSe/ CdS dot-in-rods, with a high degree of control over the rod dimensions and photoluminescence quantum yields (PL QY) ranging from 50% to 80%.…”
mentioning
confidence: 99%
“…To date, a variety of colour conversion materials are applied in displays combined with UV or blue excitation from InGaN and GaN LEDs to produce vivid colours. [20][21][22][23] II-VI group Cd based QDs, such as CdSe/CdS have been widely explored in past years due to their excellent quantum efficiency (up to film state 99% QY). The thermal quenching of these particles can be reduced by covering them with wider bandgap shell materials, e.g.…”
Section: Introductionmentioning
confidence: 99%